Comparison of conventional and electro-selective fermentations of swine manure to produce short and medium chain volatile fatty acids - Palar, Skye (Kansas State University, 2024)
Volatile fatty acids (VFAs) are produced through the microbial fermentation process. This process occurs during anaerobic digestion and VFAs are a byproduct during anaerobic degradation of complex organics. This process can be utilized and enhanced for sustainable VFA production and valorize the carbon, instead of channeling it to methane in anaerobic digesters. VFAs are valuable precursors in pharmaceuticals, food industry, biorefinery, and as electron donors in wastewater treatment. This study will specifically utilize high strength swine wastewater from a Confined Animal Feeding Operation (COD range 1000 – 20,000 mg/L) focused on the enhancement of VFA production through fermentation at varying hydraulic retention times (HRT) at three different pHs (5, 7, or 9), implemented with and without a bioanode. In this study, swine wastewater fermentation was conducted using anoxic sludge inoculum from a wastewater facility. Performance monitoring was done through VFA quantification and current density production using high-performance liquid chromatography (HPLC) and a potentiostat, respectively. At the 10-day HRT operation, both pH 5 and 9 fermenters produced acetate and propionate (34 mM and 14 mM) as the predominant VFAs, later shifting to butyrate and isocaproate (7.8 mM and 7.7 mM) and overall, a fermentation efficiency of 52% and 57.7%, respectively. Fermentation efficiency is essentially the ratio of VFA accumulation as COD to the influent COD. Acetate and isocaproate remained predominant VFAs in both pH 5 and 9 for both 5 and 2-day HRT operation. The 5-day HRT exhibited the highest fermentation efficiency at both pH 5 and 9 at 69.8% and 83.2%, respectively. During the 2-day operation, washout occurred dropping the fermentation efficiencies to 24.5% and 36.6%. When a bioanode was employed in an MEC serving as the fermentation reactor, with a poised anode potential of -300 mV (vs) Ag/AgCl, the fermentation efficiencies remained low as the anode respiring bacteria (ARB) utilize the VFAs to produce a high current density (0.5-2.2 A/m²) eventually channeled to hydrogen gas. Shorter chain VFAs such as acetate, are more readily available for the ARB to utilize which selectively enriched the dominant VFAs in the MEC to be longer chain acids such as isovalerate, valerate, and isocaproate which were more prevalent in all 10-, 5-, and 2-day operations. At the phylum level, significant enrichment of Firmicutes was observed at both pH 5 (81% at 10d; 74% at 5 d; and 64% at 2d HRTs) and pH 9 (82% at 10d; 81% at 5d; 77% at 2d). There were significant differences in selective enrichment at the genus level between the two pH conditions. While Clostridium_sensu_stricto_1 was the predominant genus at pH 5 (44% at 10d; 40% at 5d; and 23% 2 d) and pH 9 (34% at 10d; 30% at 5 d; 23% at 2d), the second predominant genus was Terrisporobacter and Turicibacter at pH 5, while it was Fastidiosipila at pH 9. The research of VFA production in wastewater treatment and implementing microbial electrochemistry techniques is becoming an increasingly important topic within the context of wastewater resource recovery. Wastewater is a huge resource to recover energy and valuable byproducts which gives waste a new life and promotes a circular economy.
Keywords: Wastewater; Volatile fatty acids; Microbial electrolysis cell